2000
DOI: 10.1038/sj.gt.3301154
|View full text |Cite
|
Sign up to set email alerts
|

Novel cell permeable motif derived from the PreS2-domain of hepatitis-B virus surface antigens

Abstract: Efficient transfer of proteins or nucleic acids across cellular membranes is a major problem in cell biology. Recently the existence of a fusogenic sequence was predicted in the junction area of the PreS2-and S-domain of the hepatitis-B virus surface antigens. We have identified cell permeability as a novel property of the PreS2-domain. Cell permeability of PreS2 is not restricted to hepatocytes. PreS2 translocates in an energy-independent manner into cells and is evenly distributed over the cytosol. Detailed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
95
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 26 publications
3
95
0
1
Order By: Relevance
“…Previous work has shown that TLM mediates an energyand receptor-independent transport across the membrane. 5 In accordance with this, neither depletion of adenosine triphosphate nor inhibition of the endocytotic machinery affected TLM-mediated membrane translocation of nucleocapsids. Moreover, no vesicle formation or plasma membrane invagination was detected by electron microscopy, confirming that the uptake is not mediated by endocytosis.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Previous work has shown that TLM mediates an energyand receptor-independent transport across the membrane. 5 In accordance with this, neither depletion of adenosine triphosphate nor inhibition of the endocytotic machinery affected TLM-mediated membrane translocation of nucleocapsids. Moreover, no vesicle formation or plasma membrane invagination was detected by electron microscopy, confirming that the uptake is not mediated by endocytosis.…”
Section: Discussionsupporting
confidence: 52%
“…5,13 Moreover, the cargo is transported directly into the cytoplasm: the endosomal compartment is not involved. 5 To investigate whether this holds true as well for the TLM-mediated transfer of nucleocapsids, the endocytotic machinery was blocked by ammonium chloride. Energy dependence was analyzed by adenosine triphosphate depetion using sodium azide.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The N-terminus has a short 24 TLM from the herpes simplex virus, which is fused in-frame to a linker (L). The TLM is 14 amino acids long whereas the linker is 19 amino acids long with a high content of G, S and T. The linker is adapted from a linker-spacer sequence used in the construction of tdTomato.…”
Section: Inducible Expression Of Hendog Promotes Cell Death In Cancermentioning
confidence: 99%